Exploring marginality among Filipino Catholics in Japan: A proposed heuristic device - Macaraan, Willard Enrique R. (Animo Repository, 2020)
The Church seeks to be inclusive; one that opens her doors to everyone. For many Filipino Catholics (FCs) in Japan, their ecclesial existence is marked by a history of negotiation as “guests” hosted by the Japanese Catholics (JCs). Within this field of host–guest interplay, this paper explores the dynamics of sociospatial seclusion by employing the ideation of marginality proffered by Loic Wacquant’s study on urban ghettos. The paper argues that the guest-identity of FCs must not be understood as a unilateral action imposed upon by the dominant hosts against the former’s subjugated narrative as powerless victims. Instead, its maintenance is perpetuated by FCs’ elective and chosen ethnic clustering. In attempt to obtain better analytical clarity of this dynamics, this paper employs the functional value of the Cartesian plane as a mapping device in plotting historical events of interplay within a spatial field. The techne inherent in the Cartesian plane is embedded with the episteme of Wacquant’s ideation. Fused together, its utility as a heuristic device is herewith proposed. It is hoped that this theoretical construct can also be useful to any analysis of marginality contained within a host–guest interplay. © 2020 by the author. Licensee MDPI, Basel, Switzerland.